2016
DOI: 10.1038/nature17405
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA sequences from the Middle Pleistocene Sima de los Huesos hominins

Abstract: A unique assemblage of 28 hominin individuals, found in Sima de los Huesos in the Sierra de Atapuerca in Spain, has recently been dated to approximately 430,000 years ago. An interesting question is how these Middle Pleistocene hominins were related to those who lived in the Late Pleistocene epoch, in particular to Neanderthals in western Eurasia and to Denisovans, a sister group of Neanderthals so far known only from southern Siberia. While the Sima de los Huesos hominins share some derived morphological feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
366
1
10

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(402 citation statements)
references
References 37 publications
25
366
1
10
Order By: Relevance
“…Our own results imply that, by the time these hominins show up in European archaeological sites, they had already separated from Denisovans. This agrees with Meyer et al (29), who show that the hominins at Sima de los Huesos were genetically more similar to Neanderthals than to Denisovans. It also agrees with Hublin (4,5), who argues that Neanderthal features emerged gradually in Europe, over an interval that began 500-600 kya.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our own results imply that, by the time these hominins show up in European archaeological sites, they had already separated from Denisovans. This agrees with Meyer et al (29), who show that the hominins at Sima de los Huesos were genetically more similar to Neanderthals than to Denisovans. It also agrees with Hublin (4,5), who argues that Neanderthal features emerged gradually in Europe, over an interval that began 500-600 kya.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, Meyer et al (29) show that 430 ky-old fossils from Sima de los Huesos, Spain are more closely related to Neanderthals than to Denisovans. This implies an early separation of the two archaic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…The Atapuerca (SH) sample conforms to this cranial morphology (23), and ancient DNA analysis has shown that the Atapuerca (SH) hominins are members of the Neandertal clade (38). The incomplete braincase from Swanscombe should probably be grouped with the Atapuerca (SH) hominins as well, even though it is more Neandertalderived in its excavated suprainiac area and its bilaterally projecting occipital torus.…”
Section: Discussionmentioning
confidence: 99%
“…This same time period also documents two major technological innovations: the expansion of the Acheulean tradition (42) and the first evidence for widespread, systematic controlled use of fire (43). Both are present at the Aroeira site, whose geographic situation in extreme southwestern Europe suggests that these innovations spread quickly throughout the European continent and were largely independent of hominin morphological diversity [although with the arrival of the Acheulean industry to Western Europe, the possibility of gene flow from outside Europe should also be taken into account (38)]. Well-dated fossils, such as the Aroeira 3 cranium, with a clear technological and ecological context are crucial to building a robust evolutionary scenario during the European Middle Pleistocene.…”
Section: Discussionmentioning
confidence: 99%
“…(45, 46), which are considered to be close to the root of the Neandertal lineage (47). It has been shown that primate species living in different habitats (e.g., rainforest canopy and open landscapes) differ in auditory capacities, and it is likely that habitat acoustics influence vocalization and audition (8-10).…”
Section: Discussionmentioning
confidence: 99%